An enhanced power harvesting from woven textile using piezoelectric materials - Chakhchaoui, N; Jaouani, H; Farhan, R; Eddiai, A; Meddad, M; Cherkaoui, O; Van Langenhove, L (IOP conference series. Materials Science and Engineering, 2020)
The field of power harvesting has experienced significant growth over the past few years due to the ever-increasing desire to produce portable and wireless electronics with extended lifespans. The present work aims to introduce an approach to harvesting electrical energy from a mechanically excited piezoelectric element and investigates a power analytical model generated by a smart structure of type polyvinylidene fluoride(PVDF) that can be stuck onto fabrics and flexible substrates. Moreover, we report the effects of various substrates and investigates the sticking of these substrates on the characterization of the piezoelectric material.